Penerapan Metode MOORA dalam Penentuan Karyawan Terbaik - Fitry AF Togatorop; Mesran Mesran (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
MOORA in the decision support system for determining the best employees performs a ranking with several stages. These stages are always carried out in the same way even though it is known that there are different input values. However, for the same input value, it will be difficult to get results in determining the ranking. The selected results will of course be carried out in an alternative order. From the research results, it is expected to determine the best employees by applying the MOORA method